ANALISIS PELAKSANAAN KEBIJAKAN PEMILIHAN KEPALA DESA SECARA SERENTAK DI KECAMATAN RANTAU PULUNG KABUPATEN KUTAI TIMUR - . Jusmiati (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article aim to analyze the Implementation of local regulation: No.7/2016 on the simultaneous Election of Village chief in the Rantau Pulung District, East Kutai Regency, and any factors that the Implementation inhibited of simultaneous election of Village Head District. This type of research is qualitative descriptive. Based on the study results as for the Implementation of local regulation: No.7/2016 on thesimultaneous election of village chief has been implemented in accordance with the local regulations but not effective yet. In which there are still obstacles in the implementation of simultaneous elections of village chief in Rantau Pulung district, because of communication rarely and information among the committee for election of village chief and budgeting disbursement retard of village chief election and coordination rarely among the committees in the election of village chief.Keyword : Election of Regional Chief, Regulation, Implementation